Development of Digital Comic Media for Learning Qira'ah for Fifth Grade Students of Madrasah Ibtidaiyah - Hijriyah, Umi; Aridan, Muhammad; Mizan, Ahmad Nur; Dealintang, Aldio; Yuniarti, Lita (Institut Agama Islam Negeri Curup, 2022)
This study aimed to develop, test the feasibility, determine the attractiveness, and determine the effectiveness of digital comic media for learning Arabic reading skills for the fifth-grade elementary school students. This was a research and development study using the ADDIE model which consisted of five stages, namely analysis, design, development, implementation, and evaluation. The data collection techniques deployed interviews, observations, documentation, and tests. The instruments were the questionnaires for validation of material experts, media experts, and linguists, and the questionnaire for students' responses to the attractiveness of the products developed. The digital comic media was classified as very feasible to be used in learning Arabic. The foregoing was evidenced by the score of feasibility test results from 2 material experts of 95% or in the very feasible category. The result of the feasibility test by 2 media experts demonstrated a score of 96% or in the very feasible category. The result of the feasibility test by linguists with a score of 76% fell into the feasible category. This digital comic media was interesting to use in learning Arabic. It was evidenced by the results of students' responses with a score of 85.57% or very interesting in the medium group trial and 85.16% or very interesting in the large group trial. This digital comic media had been proven to be able to increase students’ scores. Students’ scores increased by 32.30 with an average score of 55.65 before using the media and 88.00 after using digital comic media. The foregoing showed that the Arabic digital comic media developed by the researchers was an interesting and effective media to be used as learning media.